EFFICIENCY OF WORKING CAPITAL TO IMPROVE THE PROFITABILITY OF PT. ELNUSA TBK - Runtuwene, Christo Minardo; Pangemanan, Sifrid S.; Mekel, Peggy A. (Universitas Sam Ratulangi, 2014)
PT. Elnusa Tbk., is a company in Indonesia which is running their business in oil and gas industry. Financial performance analysis is important to set company plans and decision in order to improve their profitability. The purpose of this research is to measure the efficiency of working capital to improve the profitability of PT. Elnusa Tbk., By analyze the financial statement of PT. Elnusa Tbk., in period year 2008-2012. This research use qualitative research with descriptive method by using ratio analysis to measure efficiency level of working capital (Working capital turnover, Inventory turnover) and profit ratio (GPM, NPM, ROI, and ROE). The population of this research is all financial statement of PT. Elnusa Tbk., from year 2008-2012. The sample of this research is PT. Elnusa Tbk., audited financial statement from 2008-2012. Analysis results show that the company working capital performance is good, but not too efficient because itâ€™s not supported simultaneously with the growth of net profit margin, return on investment, and return on equity that continues to decline for some year. PT. Elnusa Tbk., must pay attention closely to their financial management, because itâ€™s important to improve the performance and also raising their profitability. The management has to more better in control of their production budget, limiting production only at peak production that still making profit. Â Keywords: efficiency of working capital, profitability